Genetic Diversity of Transcription Factor Genes in Triticum and Mining for Promising Haplotypes for Beneficial Agronomic Traits - Yang, Guang; Zhang, Ying; Wei, Xinyu; Cui, Licao; Nie, Xiaojun (Frontiers in Plant Science, 2022)
Transcription factor (TF) is a class of the sequence-specific DNA-binding proteins that modulate the transcription of target genes, and thus regulate their expressions. Variations in TF are the crucial determinants for phenotypic traits. Although much progress has been made in the functions of TF genes in wheat, one of the most important staple crops globally, the diversity of TF genes in wheat and its progenitors are not well understood, especially the agronomically promising haplotypes have not yet been characterized. Here, we identified a total of 6,023 TF genes from hexaploid wheat through a genome-search method and classified them into 59 gene families based on the conserved domain. The characteristics and dN/dS values of these genes showed evidently selective effects. Based on re-sequencing data, we found a strong genetic bottleneck among these TF genes on A and D subgenomes while no found in B subgenome during wheat domestication. Combined with selective signals and known QTLs on the whole genome, 21 TF genes were preliminarily found to be associated with yield-related traits. The haplotype frequency of these TF genes was further investigated in bread wheat and its progenitors and 13 major haplotypes were the casual loci related to key traits. Finally, the tissue-specific TF genes were also identified using RNA-seq analysis. This study provided insights into the diversity and evolution of TF genes and the identified TF genes and excellent haplotypes associating with traits will contribute to wheat genetic improvement.